2014
DOI: 10.1038/leu.2014.133
|View full text |Cite
|
Sign up to set email alerts
|

Notch and NF-kB signaling pathways regulate miR-223/FBXW7 axis in T-cell acute lymphoblastic leukemia

Abstract: Notch signaling deregulation is linked to the onset of several tumors including T-cell acute lymphoblastic leukemia (T-ALL). Deregulated microRNA (miRNA) expression is also associated with several cancers, including leukemias. However, the transcriptional regulators of miRNAs, as well as the relationships between Notch signaling and miRNA deregulation, are poorly understood. To identify miRNAs regulated by Notch pathway, we performed microarray-based miRNA profiling of several Notch-expressing T-ALL models. Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(143 citation statements)
references
References 59 publications
8
135
0
Order By: Relevance
“…11 Recent studies observed an interaction between Notch3 and p65/NF-kB to regulate T cell function under control conditions or in disease. 23,24 A pathogenic role for the Notch3 receptor was first described in CADASIL syndrome. CADASIL syndrome is a systemic arteriopathy attributed to Notch3 mutations that induce an accumulation of the extracellular domain of Notch3 in the vascular smooth muscle cells of the media layer of arteries.…”
Section: Discussionmentioning
confidence: 99%
“…11 Recent studies observed an interaction between Notch3 and p65/NF-kB to regulate T cell function under control conditions or in disease. 23,24 A pathogenic role for the Notch3 receptor was first described in CADASIL syndrome. CADASIL syndrome is a systemic arteriopathy attributed to Notch3 mutations that induce an accumulation of the extracellular domain of Notch3 in the vascular smooth muscle cells of the media layer of arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Notch1 blocking antibodies MHN1-519 were purchased from BioLegend, and the treatment was performed as previously described. 55,56 Notch1 Val1744, Fbxw7 were purchased from Cell Signaling Technology. Blots were incubated for 2 h at room temperature or with an anti-Notch1 Val1744 (Cell Signaling Technology) overnight at 4 °C according Cell Signaling manufacturer's instruction.…”
Section: Reagentsmentioning
confidence: 99%
“…This can occur via a perfect complimentary binding of the miRNA to the target mRNA (endonucleolytic cleavage of the mRNA) or by an imperfect complimentary binding to the target mRNA (translation repression). 32 Due to their cell cycle interference, miRNAs are involved either as oncogenes or as oncosuppressors in the pathogenesis of a huge variety of human cancers such as lung cancer, 33,34 prostate cancer, 35 colorectal cancer, 36,37 leukemia, [38][39][40] gliomas 41 and medulloblastoma, 42 diffuse large B-cell lymphoma, 43 hepatocellular carcinoma (HCC), 44 gastric cancer, 45,46 osteosarcoma, 47 renal cell carcinoma, 48 BC, 49 and OC. 50 Particularly, their presence in the blood has been shown to be associated with histology, clinical stage, survival, and oncogenic expression in OC and BC.…”
Section: Introductionmentioning
confidence: 99%